Management of giant adrenal schwannoma - Oberoi, Ajit; Kataria, Kamal; Prakash, Om; Yadav, Rajni; Goyal, Ankur (International Surgery Journal, 2019)
Adrenal schwannoma is a rare differential of adrenal incidentaloma with scarce literature available at present. Adrenal schwannomas are usually non-secreting tumours but can very rarely secrete catecholamines. Specimen of our patient was 14 cm in diameter and weighed 900 gm which is the largest adrenal schwannoma in literature. Although it is a benign lesion but there are no standard treatment guidelines because of rarity of lesion.